PERSEPSI PESERTA DIDIK TENTANG PENGUASAAN TEKNIK KONSELING INDIVIDUAL OLEH GURU BIMBINGAN DAN KONSELING - Zulvia Trinova; Putri Silvia (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2017)
This research was motivated that the teacher of guidance and counseling minimally applied the individual counseling technique in conducting counseling to the learners. The teacher of guidance and counseling mostly used technique of giving advice only. Beside that, learners did not trust the teacher guidance and counseling to reveal all their problems because the teacher was less friendly in welcoming the learners. The formulation of the problem in this research was how the perception of learners about the mastery of individual counseling techniques applied by guidance and counseling teachers in SMP N 2 Bayang. The limitations of the problem of this study is the perception of learners about the mastery of welcoming techniques, empathy techniques, open questions techniques employed by teachers guidance and counseling in individual counseling in SMP N 2 Bayang. This study aims to determine the perceptions of learners about the mastery of welcoming techniques, empathy techniques, open questions technique used by teachers guidance and counseling in individual counseling in SMP N 2 Bayang.This research method was descriptive quantitative by using percentage formula and the instrument was questionnaire. The technique is taking the sample was Purpossive Sampling. The results revealed that the perception of learners about the mastery of welcoming student techniques by teachers guidance and counseling in SMP N 2 Bayang was classified as less well. The perception of learners about mastery of empathy techniques to learners by teacher guidance and counseling at SMP N 2 Bayang was classified quite well. The student's perception about mastery of open questioning technique to learners by teacher guidance and counseling at SMP N 2 Bayang was classified as less good.